Optical fiber sensor for Hg(II) based on carbon dots - Goncalves, HMR (2010)
An optical fiber sensor for Hg(II) in aqueous solution based on sol-gel immobilized carbon dots nanoparticles functionalized with PEG(200) and N-acetyl-t-cysteine is described. This sol-gel method generated a thin (about 750 nm), homogenous and smooth (roughness of 2.7 +/- 0.7 a) film that immobilizes the carbon dots and allows reversible sensing of Hg(II) in aqueous solution. A fast (less than 10 s), reversible and stable (the fluorescence intensity measurements oscillate less than 1% after several calibration cycles) sensor system was obtained. The sensor allow the detection of submicron molar concentrations of Hg(II) in aqueous solution. The fluorescence intensity of the immobilized carbon dots is quenched by the presence of Hg(II) with a Stern-Volmer constant (pH = 6.8) of 5.3 x 10(5) M(-1).